Ecosystem Approach to Assessing the State of the Urbanized Environment. Issue 2 (February 2020) - Avdeeva, E; Panov, A
Abstract: The intensive process of urbanization has led to a number of environmental problems associated with a sharp deterioration in the quality of the urban environment. All this necessitates an objective assessment of its current state and knowledge of the mechanisms of functioning of systems in the interests of human ecological safety under the conditions of anthropogenic stress. Coniferous plants are used in urban landscaping. Under urban conditions, conifers perform the role of biological indicators, while the assimilation apparatus is a marker feature, which allows assessing the environmental conditions of urban areas. Pine ( Pinus sylvestris L. ) is used in gardening of city streets and recreation areas. At the same time, pine ordinary responds to the effects of the urbanized environment. The results of the assessment of the state of the air environment by the dendroindication method based on the morphological features of conifers showed that of the 22 surveyed objects, only 3 of the air condition are estimated to be clean in the area village, the main building of the Siberian Federal University and on Botanical Boulevard. At two sites, the state of the air environment is estimated as clean, three - relatively clean. These objects are located on the periphery of the city, one of them in the valley of the river. On the remaining objects, the state of the air environment is estimated from polluted (5 objects), dirty (6 objects) to very dirty (2 objects).